2015
DOI: 10.1002/ijc.29939
|View full text |Cite
|
Sign up to set email alerts
|

CD90+ stromal cells are the major source of IL‐6, which supports cancer stem‐like cells and inflammation in colorectal cancer

Abstract: IL-6 is a pleiotropic cytokine increased in CRC and known to directly promote tumor growth. Colonic myofibroblasts/fibroblasts (CMFs or stromal cells) are CD90+ innate immune cells representing up to 30% of normal colonic mucosal lamina propria cells. They are expanded in CRC tumor stroma, where they also known as a cancer associated fibroblasts (CAFs). Cells of mesenchymal origin, such as normal myofibroblasts/fibroblasts, are known to secrete IL-6; however their contribution to the increase in IL-6 in CRC an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 50 publications
0
78
0
Order By: Relevance
“…On multivariate survival analysis (Table 5) Although failing to reach statistical significance, the density of tumour-associated stroma, as measured by TSP, appeared to be associated with pSTAT3 expression. Given that an increase in TSP primarily reflects an increased population of cancer-associated fibroblasts within the tumour microenvironment, this would further support the importance of IL-6 secretion by fibroblasts in the activation of the JAK/STAT3 pathway in tumour cells (14,15).…”
Section: P=0039)mentioning
confidence: 84%
See 2 more Smart Citations
“…On multivariate survival analysis (Table 5) Although failing to reach statistical significance, the density of tumour-associated stroma, as measured by TSP, appeared to be associated with pSTAT3 expression. Given that an increase in TSP primarily reflects an increased population of cancer-associated fibroblasts within the tumour microenvironment, this would further support the importance of IL-6 secretion by fibroblasts in the activation of the JAK/STAT3 pathway in tumour cells (14,15).…”
Section: P=0039)mentioning
confidence: 84%
“…Circulating IL-6 is commonly elevated in a number of cancers, including colorectal cancer (11)(12)(13), and is the predominant stimulus for the hepatic synthesis of acute phase proteins, including CRP (6). Cancer-associated fibroblasts and inflammatory cells contribute to high levels of IL-6 within the tumour microenvironment (14,15), with subsequent tumour cell activation of the soluble IL-6 receptor/ glycoprotein 130 complex (16). Interleukin-6 trans-signalling regulates JAK activity within the tumour cell to promote phosphorylation of the tyrosine 705 residue of STAT3.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3b, Extended Table 4a-c). THY1 has been associated with populations of fibroblasts with activated features in tissues 56,57 and with secretion of proinflammatory cytokines in the context of diseases 58,59 . FACS analysis using antibodies to THY1 and to the pan-fibroblast marker PDGFRα 60 confirmed that old fibroblast cultures in general contained a higher proportion of THY1-positive/PDGFRα-positive cells (hereafter termed THY1+ cells) (Fig.…”
Section: Mainmentioning
confidence: 99%
“…Several studies have now suggested that CD90 + IMSC may be crucial regulators of gut homeostasis (Huynh et al, 2016; Karpus et al, 2019; Kinchen et al, 2018; Powell et al, 2011; Roulis et al, 2014). However, recent efforts to understand the heterogeneity and function of ISMC using single-cell RNA sequencing (scRNA-seq) and lineage tracing techniques have revealed the existence of multiple functionally distinct subsets (Kinchen et al, 2018; Nanki et al, 2018), many of which produce soluble factors and cytokines likely capable of modulating gut homeostasis and epithelial integrity (Han et al, 2018; Kinchen et al, 2018; Shoshkes-Carmel et al, 2018; Thomson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%